Ego functions and their connections with coping strategies in adolescents with conduct disorders - Kalpokienė, Vaida; Gudaitė, Gražina (Psichologija, 2007)
Ego is one of the fundamental formations of personality, which secures inner and outer adaptation. Its role must be very strong in adolescence when a person must adjust with various inner and outer demands. Adaptation of adolescents with conduct disorders is largely dysfunctional, that’s why we raise a question about suchlike teenager’s Ego functions and their interconnection with coping strategies (which determines adaptation to external requirements). 38 adolescents with conduct disorders and 35 healthy adolescents participated in this research. Age of participants was from 14 to 16 years. Teenagers for the research were screened by using Youth Self Report Questionnaire (YSR11/18) (Achenbach and Rescorla, 2001). Ego functions (relations with objects, control of affects and impulses, defensive functioning, synthetic – integrative functioning) were evaluated using clinical interview for the assessment of Ego functions (Bellak et al., 1973). Coping strategies were evaluated with COPE questionnaire (Carver et al., 1989). The research data showed that Ego functions of teenagers with conduct disorders are more disturbed than Ego functions of healthy ones (p < 0.01), especially this is noticeable on the control of affects and impulses. Only two Ego functions of adolescents with conduct disorder are statistically correlated: object relations and synthetic-integrative functioning; while all Ego functions of healthy adolescents have statistically significant correlations. However after the comparison of correlative matrixes we found no statistically significant differences between those matrixes (χ2 = 10.1794, df = 6, p = 0.1173). Adolescents with conduct disorders are applying two less adaptive coping strategies regularly: behavioral disengagement (p = 0.001) and alcohol – drug disengagement (p < 0.001). Also they are using one emotion-focused coping strategy denial (p < 0.05). Healthy adolescents are applying two problem-focused coping strategies regularly: active coping (p < 0.05) and restraint coping (p < 0.05). They also are using emotion-focused coping strategy positive reinterpretation and growth (p < 0.05). Ailing teenagers are using less adaptive coping strategies more often (p < 0.05). The research showed, that coping strategies (problem-focused coping, emotion-focused coping and less adaptive coping) are related with one of Ego functions-defensive functioning (teenagers with conduct disorders R = 0.619, R² = 0.383, p = 0.001; healthy adolescents R = 0.605, R² = 0.366, p = 0.002). This once more shows us that these psychological processes are closely related to each other and that adaptation needs interaction between conscious and unconscious processes.
Keywords: conduct disorders; adolescents; Ego functions; coping strategies